Investigation of popliteal artery branching patterns in magnetic resonance angiography examinations: Experience of Kayseri Education and Research Hospital - Aysel Özaşlamacı (KARE Publishing, 2019)
Objective: This study was designed to evaluate variations in popliteal artery (PA) distal branching observed in lower extremity magnetic resonance angiography (MRA) images. Methods: A total of 576 lower extremity MRA examinations that were performed consecutively between 2008 and 2012 in a single hospital were retrospectively evaluated. In all, 767 lower extremity images of 425 patients were included in the study and 151 examinations that were inappropriate were excluded. A bilateral evaluation was conducted of 342 lower extremities, and 83 lower extremities were evaluated unilaterally. The anatomical variations in the PA branching patterns were classified and assessed, and the results were evaluated with other studies that have examined PA distal branching variations with digital subtraction angiography and computed tomography angiography. Results: The most frequently seen pattern was type IA (normal pattern), detected in 613 (80%) extremities. Variations in PA branching were depicted in 154 (20%) extremities and 733 (95.6%) limbs had a normal level of PA branching. Type II variations, with a high division of the PA (at or above the level of the tibial plateau), were seen in 34 (4.4%) extremities. Type III variations were observed in 87 (11.4%) extremities. Of the 342 bilaterally evaluated patients, 251 (73%) had a bilaterally symmetrical pattern. Type IA was the most frequently encountered bilaterally symmetrical pattern. Conclusion: MRA examination can be used as an alternative to digital subtraction angiography for the evaluation of PA branching patterns.